Principles of synthetic intelligence Psi, an architecture of motivated cognition - Bach, Joscha (Oxford : Oxford University Press, 2009)
This title features chapters on machines to explain the mind Domer's 'blueprint for a mind', representation of and for mental processes, language and future avenues, from PSI to microPSI and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cognition; Artificial intelligence